Application of Taylor-Newton homotopy method for solving electrical engineering design problem - Hasan, Talib Hashim; Azram, Mohammad; Daoud, Jamal Ibrahim (2010)
We describe simple implementations of homotopy (also called continuation) algorithm for determining the proper resistor to dissipate energy at a specified rate of an electric circuit. Homotopy algorithm can be considered as a developing of the classical methods in numerical computing such as Newton- Raphson and fixed point methods. In homoptopy methods, an embedding parameter is used to control the convergence. The method purposed in this work utilizes a special homotopy called Newton homotopy. Numerical example solved in MATLAB is given to show the effectiveness of the purposed method